Safety and efficacy of a feed additive consisting of zinc chelate of amino acids hydrate for all animal species (Zinpro Animal Nutrition (Europe) Inc.). (29th October 2021) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Fašmon Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of zinc chelate of amino acids hydrate, brand name Availa ® Zn, for all animal species, based on a dossier submitted for the modification of the terms of the authorisation of the additive. The additive is currently authorised using amino acids derived from soya protein with a minimum content of 10% zinc. The applicant proposed (i) to include amino acids from other sources such as hydrolysed corn gluten, hydrolysed potato protein and hydrolysed poultry feather meal; (ii) to introduce a minimum specification for free amino acids of 17%; (iii) to introduce a tighter specification of the zinc content of 10–11%. The additive, produced using different proposed sources of hydrolysed proteins, complies with the specifications set by Commission Regulation (EU) 2016/1095. The FEEDAP Panel considers that the use of the different proposed sources of hydrolysed proteins (i.e. soy, feather meal, potato and corn gluten) do not modify the conclusions reached in the previous assessments on the safety for the target species, consumers, environment and efficacy of the additive above. Concerning the safety for the users, the additive should be considered as a skin and eye irritant and a skin sensitiser. The additive has a high dusting potential; however, in the absence of data on the concentration of zinc in the dust it is not possible to make the assessment of the exposure by inhalation.